2010
DOI: 10.1590/s1677-55382010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking impairs sperm bioenergetics

Abstract: Objective: The growing consensus on the negative impact of cigarette smoking on fertility prompted us to compare the rate of sperm respiration in smokers and non-smokers. Materials and Methods: Semen samples from 20 smokers and 58 non-smokers consulting at the andrology laboratory for fertility evaluation were used. Smoking was defined as consumption of at least a half a pack per day. A phosphorescence analyzer that measures O 2 concentration in sperm suspensions as function of time was used to determine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Similar effects of automobile exhausts on the FVC and FEV 1 have been reported in tunnel and bridge workers & traffic police. [3][4][5][6] FEF is considered a fairly good test to identify early small airway disease. [7][8][9] The findings of the present study indicate that small airways probably bear the brunt of the air pollution & fuel vapour related lung injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects of automobile exhausts on the FVC and FEV 1 have been reported in tunnel and bridge workers & traffic police. [3][4][5][6] FEF is considered a fairly good test to identify early small airway disease. [7][8][9] The findings of the present study indicate that small airways probably bear the brunt of the air pollution & fuel vapour related lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with most studies on pollution inflicted changes in lung functions. [5,10,11] In combination with particulate pollutants, SO 2 and NO 2 have a greater chance to reach the deeper parts of the lungs. The gaseous pollutants may also alter the properties and concentration of surfactant and may thus contribute to the early closure of small airways.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, Chohan et al found that there are no differences between smokers and non-smokers for ejaculate volume, motility, concentration and sperm morphology. 18 However, in an another study it is reported that smokers had significantly less spermatozoa. 19 In a study, Yardımcı et al reported that exposure to cigarette smoke decreases the testosterone level and Leydig cell number in rats.…”
Section: Discussionmentioning
confidence: 91%
“…In literature, there are several cross-sectional studies about the effects of active or passive smoking on semen quality or testicular hormone levels, but most of which have included adolescent or adult patients or have been done in rats. 12,14,17,18 Some studies have shown a negative effect of smoking on semen quality in terms of the conventional semen characteristics whereas others could not demonstrate such an effect. 12,17 Furthermore, it has not been clarified whether smoking has an impact on levels of male reproductive hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been shown that cigarette smoke is able to alter sperm density, motility, morphology and seminal fluid leukocyte concentration. Effects of the cigarette smoke on sperm DNA integrity, aneuploidy rate, production of free oxygen radicals (ROS) have been evaluated, but the results of these studies appear conflicting: some have shown a negative effect (Stillman et al, 1986; Close et al, 1990; Pacifici et al, 1993; Sofikitis et al, 1995; Vine et al, 1996; Curtis et al, 1997; Rubes et al, 1998; Zhang et al, 2000; Saleh et al, 2002; Kunzle et al, 2003; Said et al, 2005; Sepaniak et al, 2006; Gaur et al, 2007; Reina Bouvet et al, 2007; Calogero et al, 2009; Chohan and Badawy, 2010; El-Melegy and Ali, 2011), while others reported no effect (Vogt et al, 1986; Dikshit et al, 1987; Oldereid et al, 1989; Lewin et al, 1991; Belcheva et al, 2004). …”
Section: Introductionmentioning
confidence: 99%